Clinical Research on the Postoperative Recurrence of Non Muscle-Invasive Bladder Cancer - Xu, Hui; Xu, Chang-Li; Song, Jin-Qi; Zhou, Ya-Nan (Nepalese Journal of Cancer, 2018)
Background: Bladder cancer is a common malignant tumor in the urinary system, in which non muscle-invasive bladder cancer (NMIBC) is the most common. The recurrence rate of the patients after operation is high, which has a serious impact on the physical and mental health of the patients. Therefore, how to reduce the recurrence rate of NMIBC patients is the focus of clinical research. Objectives: To study the recurrent factor of NMIBC after surgery for promotion of therapeutic efficacy. Methods: Retrospective analysis of one hundred patients of carcinoma of urinary bladder were consecutively enrolled and data on gender, age, tumor stage, tumor grade, tumor size, tumor configuration, multiplicity, date of surgery, tumor histology, recurrence history, resident area, frequency of tumor recurrence, follow-up history as screening target to analyze by Cox proportional-risk model, and screen dependent factor which can be used to predict tumor recurrent risk after surgery. Results: Tumor size, tumor stage, tumor grade, frequency of tumor recurrence, multiplicity and history of regular follow-up are related to NMIBC recurrence after surgery. Conclusion: Aggregate analysis of these factors can evaluate recurrent risk of NMIBC and it is significant to the therapy of NMIBC.